Outage Probability Analysis of Decode-and-Forward Relaying Systems with Energy Harvesting - Cheng, Gefan; Sun, Hao; He, Xin; Jiang, Weiwei; Zhou, Xiaobo; Cheng, Meng; Yang, Panlong (2018 4th International Conference on Big Data Computing and Communications (BIGCOM), 2018)
This paper investigates the outage performance analysis of a decode-and-forward (DF) relaying system with simultaneous wireless information and power transfer (SWIPT). The system consists of a source, a relay as well as a destination. The direct link between the source and the destination is assumed. The relay employs power splitting (PS) strategy for the SWIPT to split the received power for information processing and energy harvesting. Based on DF, the relay forwards the source information using the harvested energy if it successfully decodes the information. The destination performs joint decoding (JD) if the relay is active or single decoding otherwise. The outage probability of the proposed system is then derived from the viewpoint of the source coding with side information theorem. Furthermore, the outage probability for the SWIPT-based DF relaying system without direct link is presented as a baseline. The simulation results verify that the proposed scheme outperforms the baseline in terms of outage probability with significant gains. In addition, the effect of distances between nodes on the PS ratio is also evaluated through computer simulations.